Long Non-Coding RNAs in the Pathogenesis of Diabetic Kidney Disease - Hu, Mengsi; Ma, Qiqi; Liu, Bing; Wang, Qianhui; Zhang, Tingwei; Huang, Tongtong; Lv, Zhimei (Frontiers in Cell and Developmental Biology, 2022)
Diabetic kidney disease (DKD) is one of the major microvascular complications of diabetes mellitus, with relatively high morbidity and mortality globally but still in-short therapeutic options. Over the decades, a large body of data have demonstrated that oxidative stress, inflammatory responses, hemodynamic disorders etc. might exert critical influence in the initiation and development of DKD, whereas the delicate pathogenesis of DKD remain profoundly elusive. Recently, long non-coding RNAs (lncRNAs), extensively studied in the field of cancer, are attracting increasing attentions on the development of diabetes mellitus and its complications including DKD, diabetic retinopathy and diabetic cardiomyopathy. In this review, we chiefly focused on abnormal expression and function of lncRNAs in major resident cells (mesangial cell, endothelial cell, podocyte and tubular epithelial cell) in the kidney, summarized the critical roles of lncRNAs in the pathogenesis of DKD, and elaborated their potential therapeutic significance, in order to advance our knowledge of this field, which might help in future research and clinical treatment for the disease.